Perancangan Galeri Seni Lukis Ivan Hariyanto Di Surabaya - Santoso, Vania (Intra, 2014)
Paintings become one of the most important thing for decoration element nowadays, besides wants and needs of people about paintings for decoration element which its purpose to make rooms becomes more beautiful is very high. Making design work on "Design Paintings Gallery Ivan Hariyanto in Surabaya" This is becoming a vessel that holds and supports Ivan Hariyantoâ€™s paintings on display so that it becomes permanent gallery in Surabaya where tourists both domestic and abroad can enjoy and visit at any time without waiting special exhibitions and events without deadlines. Using linear design method, the target will be designing concept that taken from the paintings of Ivan Hariyanto, so the interior design in the gallery isÂ  made to have a relationship and support each Hariyanto Ivan works on display, and prototype using 1: 100 scale.